The Quequén Salado river basin: Geology and biochronostratigraphy of the Mio-Pliocene boundary in the southern Pampean plain, Argentina - Beilinson, Elisa (2017)
The Quequén Salado river basin has been the focus of several contributions since the first decades of the XX century, namely dealing with the general geological features of the deposits and with the vertebrate remains. In this paper, the Neogene geological history documented by the Quequén Salado river exposures is reconstructed by means of stratigraphic, sedimentological and paleomagnetic studies along with the paleontological analysis of vertebrate remains. The study area is a crucial setting not only to better understand the evolution of the southern Pampas basin during the late Miocene-early Pliocene interval, but also to test the validity of the biochronologic and biostratigraphic schemes, especially the “Irenense”. A geological model for the Quequén Salado river valley is proposed: a case of downcutting and headward erosion that contributes with a coherent interpretation to explain the spatial distribution of facies and fossil taxa: the younger in the distal sector of the Quequén Salado middle basin and the older in the lower basin. The sedimentary record is believed to represent the distal reaches of a distributary fluvial system that drained from the Ventania ranges. The stratigraphic section of Paso del Indio Rico results a key stratigraphic site to fully understand the stratigraphic nature of the boundary between the Miocene and the Pliocene (the Huayquerian and Montehermosan stages/ages). In this sense, two stratigraphically superposed range zones have been recognized in the area: Xenodontomys ellipticus Range Zone (latest Miocene-early Pliocene; late Huayquerian), and Eumysops laeviplicatus Range Zone (early Pliocene; Montehermosan). Taking into account the available geological and paleontological evidences, the “Irenense” would not represent a valid biostratigraphic unit, since, according to the geological model here proposed, it would be represented by elements of the Xenodontomys ellipticus Range Zone in the lower QS basin and by elements of the Eumysops laeviplicatus Range Zone in the middle QS basin.